Conversion issue in Malaysia: A challenge to religion and racial harmony - Yussof, Sheila Ainon (International Institute of Advanced Islamic Studies Malaysia (IAIS), 2014)
There is a worrying trend recently of inter-religious cases which have fuelled angst amongst multiracial communities in Malaysia, and which threaten to disrupt racial harmony or dismantle the 1Malaysia Unity Framework. We refer to the recent case of a “Muslim” bride (named Zarina Majid) marrying her Hindu boyfriend of seven years.